Early postoperative efficacy of a fully automated orthopedic robotic system-assisted percutaneous pedicle screw fixation for isthmic spondylolisthesis - Li Zongze; Cheng Yongquan; Zeng Guanjie; Zhu Yongjian; Cui Yuhui; Jiang Hui; Chen Jianting (Computer Assisted Surgery)
To assess the feasibility of percutaneous pedicle screw fixation assisted by a fully automated orthopedic robotic system for the treatment of isthmic spondylolisthesis and evaluate its early postoperative outcome. Totally 20 patients with isthmic spondylolisthesis who underwent surgical procedure by the same medical group from March 2020 to March 2023 were retrospectively analyzed, including 10 patients in the robot-assisted group (RA group) and the other 10 patients in the conventional free-hand technique group (FH group). Accuracy of screw insertion was determined using the Gertzbein-Robbins Scale. The accuracy of the novel robotic system was evaluated by comparing the screw position in the preoperative planning and measuring the entry point deviation distance and the trajectory rotation. The differences in operative time, intraoperative blood loss, radiographic fluoroscopy time and fluoroscopic dosage, and length of hospital stay were compared between the two groups. The lumbar visual analog scale scores before and 7 days after operation were analyzed to evaluate the improvement of low back pain as the early postoperative outcome. A total of 84 pedicle screws were placed. In the RA group, 97.5% of screws were Grade A, and 2.5% were Grade B. In the FH group, 88.6% of screws were Grade A, 9.1% were Grade B, and 2.3% were Grade C. No statistical difference was found in the operation time between two groups. The RA group showed a significant reduction in intraoperative blood loss, radiographic fluoroscopy time and fluoroscopic dosage, and length of hospital stay compared to the FH group. The low back pain in both groups was significantly improved after the operation. The novel orthopedic robotic system-assisted percutaneous pedicle screw fixation, with accurate intraoperative screw placement, less surgical damage, less fluoroscopy and shorter length of hospital stay, can be safe and effective for the surgical treatment of isthmic spondylolisthesis.